Expanded Carrier Screening in Reproductive Medicine—Points to Consider: A Joint Statement of the American College of Medical Genetics and Genomics, American College of Obstetricians and Gynecologists, National Society of Genetic Counselors, Perinatal Quality Foundation, and Society for Maternal-Fetal Medicine. Issue 3 (March 2015) - Edwards, Janice G.; Feldman, Gerald; Goldberg, James; Gregg, Anthony R.; Norton, Mary E.; Rose, Nancy C.; Schneider, Adele; Stoll, Katie; Wapner, Ronald; Watson, Michael S.
Abstract : The Perinatal Quality Foundation and the American College of Medical Genetics and Genomics, in association with the American College of Obstetricians and Gynecologists, the Society for Maternal-Fetal Medicine, and the National Society of Genetic Counselors, have collaborated to provide education for clinicians and laboratories regarding the use of expanded genetic carrier screening in reproductive medicine. This statement does not replace current screening guidelines, which are published by individual organizations to direct the practice of their constituents. As organizations develop practice guidelines for expanded carrier screening, further direction is likely. The current statement demonstrates an approach for health care providers and laboratories who wish to or who are currently offering expanded carrier screening to their patients. Abstract : Points to consider in the use of expanded carrier screening are provided for clinicians and laboratories.